Global Reconstruction of Educational Attainment, 1950 to 2015: Methodology and Assessment - Markus Speringer; Anne Goujon; Samir KC; Michaela Potančoková; Claudia Reiter; Sandra Jurasszovich; Jakob Eder (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2019)
This paper documents the rationale, the data and the methodology for reconstructing the population of 185 countries by levels of educational attainment for the period 1950-2015, by age and sex. The reconstruction uses four main input types for each country: (1) The most recent and reliable education structure by age and sex, (2) any reliable historical education data by age and sex to use as marker points in the reconstruction to increase output accuracy, (3) a set of age- and sex-specific mortality differentials and education transition by education and (4) population estimates by age and sex. The methodology relies on the fact that education is acquired at young ages and does not change much over the life course. In the first part we present the reconstruction principle. In the second one, we document the methodology and the data. The third section compares the reconstructed estimates to other existing estimates including the past reconstruction effort of the Wittgenstein Centre for Demography and Human Capital. The data are available at: www.wittgensteincentre.org/dataexplorer (version 2.0). Supplementary to this Working Paper a detailed data documentation Excel file can be downloaded via: https://www.oeaw.ac.at/vid/publications/serial-publications/vid-working-papers/.
Keywords: 300; Educational attainment; human capital; reconstruction; back-projection; modelling